(untitled) (Baltic Journal of Sport and Health Sciences, 2013)
Research background. The notion of tolerance is used in various contexts, but nevertheless it remains ambiguous. The very fact that educators, politicians, and philosophers again and again face questions about the meaning of value term “tolerance”, stresses the vivid necessity of continuous attempts to elucidate the notion of tolerance at the theoretical level. Research aim was to provide relevant arguments for the thesis that tolerance is a context dependent notion and therefore the claims about tolerance “in general” are ambiguous, uninformative, and non-instructive. Research method. Our research methodology was philosophical reflection involving conceptual analysis and the application of the outcomes to education sciences. Research results. If we are to understand and define the concept of tolerance, we need a broader understanding of what is good and what is bad, understanding of what behaviour is expected from us under certain cultural circumstances. Discussion and conclusions. 1. In religious context, tolerance is a respectful attitude towards beliefs and practices of others – attitude which, in fact, can be grounded either by dogmatism or by scepticism. 2. In political context, emphasis is laid not on what others believe or think, but on what people do. 3. There is one common feature of tolerance conceptions which take shape in inter-religious discourse and in politics: it is believed that it is quite easy to understand the motives of actions performed by “others”; such understanding (“empathy”) is the main condition for tolerance. 4. In ethics and education, tolerance is the measurement (or objective assessment) of our beliefs keeping in mind possibilities of their alternatives. In this respect, tolerance is the realization of human rational nature. Keywords: tolerance, tolerance education, autonomy, ethics, rationality.